2011
DOI: 10.1257/aer.101.2.819
|View full text |Cite
|
Sign up to set email alerts
|

Deferred Compensation in Multiperiod Labor Contracts: An Experimental Test of Lazear's Model

Abstract: This paper provides the first experimental test of Edward Lazear's (1979) model of deferred compensation. We examine the relationship between firms' wage offers and workers' effort supply in a multi-period environment. If firms can ex ante commit to a wage schedule with deferred compensation, workers should respond by supplying sufficient effort to avoid dismissal. We contrast this full-commitment case to controls with no commitment and computer-generated wages in order to examine the roles of monetary incenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
(21 reference statements)
1
27
0
Order By: Relevance
“…Taken together, in our view the recent findings of Huck et al (2011) and the results reported in the present paper suggest that more experimental work on the incentive effects of long-term contracts guided by contract-theoretic research might be very promising.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Taken together, in our view the recent findings of Huck et al (2011) and the results reported in the present paper suggest that more experimental work on the incentive effects of long-term contracts guided by contract-theoretic research might be very promising.…”
supporting
confidence: 80%
“…To our knowledge, Huck et al (2011) is the only other experiment exploring the intertemporal allocation of wages. They test Lazear's (1979) theory of deferred compensation (i.e., wage profiles that are increasing over a worker's lifetime; cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) The deadline for inclusion in the study was that the paper should be published or posted as accepted/in press at the website of the journal at August 1, 2014. There are a number of different possible experimental designs. The most "classical" design is the randomized controlled trial (RCT) design, where participants are randomly allocated to two or more treatments and the outcome is compared between treatments.…”
Section: Replicationsmentioning
confidence: 99%